Role of social welfare personnel for assisting children in conflict with law at ogan ilir regency juvenile social rehabilitation center - Dita Mayreista; Nurul Nurul (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This study aims to examine the regulatory framework and concrete role of Tenaga Kesejahteraan Sosial (TKS) in assisting the social rehabilitation process of Anak Berhadapan dengan Hukum (ABH) within the Indonesian juvenile justice system, specifically evaluating their effectiveness in a local context. Research Methodology: This study employs a socio-legal research method, integrating a statutory analysis of Law No. 11/2012 with a conceptual exploration of restorative justice. Empirical data were gathered at the Ogan Ilir Regency Juvenile Social Rehabilitation Center through literature reviews, direct observations, and in-depth interviews with key informants, including three TKS representatives and one juvenile client. Results: The findings reveal that although the Indonesian legal system prioritizes restorative justice and diversion, field implementation faces significant challenges due to the diverse characteristics and emotional instability of foster children. Success is achieved when TKS prioritize trust-building, holistic needs identification, and the delivery of integrated vocational and spiritual guidance to restore their confidence. Conclusions: Macro-level regulations effectively position children as national assets through restorative paradigms. On a practical level, the role of TKS remains vital as facilitators and advocates who successfully restore dignity and future hope through adaptive, flexible, and individualized assistance strategies. Limitations: The study's scope is limited to the Ogan Ilir Regency Juvenile Social Rehabilitation Center, focusing solely on the specific roles of TKS within this local institutional environment. Contributions: This research contributes to the social welfare and juvenile justice disciplines by addressing data gaps regarding professional TKS effectiveness in social recovery and the protection of children’s fundamental rights.